2020
DOI: 10.37506/v11/i1/2020/ijphrd/194103
|View full text |Cite
|
Sign up to set email alerts
|

Is there an Effect of Serotonin on Attention Deficit Hyperactivity Disorder

Abstract: Background: Attention deficit hyperactivity disorder (ADHD) is a neurobiological disorder with a prevalence of 5%-10% in the world that negatively impacts school behavior and achievement. There have been many studies reveals that attention disorders are caused by the decreased levels of dopamine and norepinephrine neurotransmitter. However, particular concern nowadays are the emotional and behavioral problems. The emotional and behavioral problem is suspected to be caused by the decrease in serotonin level. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Changes in Tryp metabolism have been consistently associated with the pathogenesis of various neuropsychiatric diseases [ 1 , 9 , 10 , 14 , 18 , 19 , 20 ]. Specifically, alterations in 5-HTergic function have been observed in epilepsy and psychiatric conditions such as depression, ADHD, ASD, and OCD [ 19 , 27 , 97 , 98 ]. In contrast, changes in the kynurenine pathway have been established as key players in inflammation-associated disorders, as well as for epilepsy, and neurodegenerative and autoimmune disorders [ 10 , 14 , 20 , 99 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in Tryp metabolism have been consistently associated with the pathogenesis of various neuropsychiatric diseases [ 1 , 9 , 10 , 14 , 18 , 19 , 20 ]. Specifically, alterations in 5-HTergic function have been observed in epilepsy and psychiatric conditions such as depression, ADHD, ASD, and OCD [ 19 , 27 , 97 , 98 ]. In contrast, changes in the kynurenine pathway have been established as key players in inflammation-associated disorders, as well as for epilepsy, and neurodegenerative and autoimmune disorders [ 10 , 14 , 20 , 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…On one hand, most neuropsychiatric disorders with aggravated manifestations in women (e.g., mood disorders) are associated with deficient production of 5-HT [ 25 , 26 ]. On the other hand, neuropsychiatric conditions that affect more males than females (e.g., ASD and ADHD) have excessive production of that neurotransmitter [ 10 , 24 , 27 ]. Sex differences are also seen in neurodegenerative and autoimmune disorders, as the male sex is a significant risk factor for Parkinson’s disease (PD) and motor neuron disease, whilst females are more susceptible to Alzheimer’s disease (AD) and multiple sclerosis [ 22 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…This disorder represents a serious problem for children, parents, and teachers, as children have difficulties in performing daily activities at home and school. In addition, parents have pay more attention to their child, which can even lead them to stop working [42], and at school, a child with ADHD demands more attention from his teachers, significantly affecting their workload [43].…”
Section: Adhdmentioning
confidence: 99%
“…3 Department of Psychiatric, Faculty of Medicine Universitas Airlangga, Dr. Soetomo General Hospital, Surabaya, Indonesia. 4 Department of Microbiology, Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia.…”
Section: Fundingmentioning
confidence: 99%
“…In addition, it is reported that parents tend to resign from their jobs to provide more attention to their ADHD children. Children with ADHD also need extra help from their teachers at school, but such assistance is not always optimally provided due to the workload of said teachers [ 4 ].…”
Section: Introductionmentioning
confidence: 99%